Epigenetic silencing of p21 by long non-coding RNA HOTAIR is involved in the cell cycle disorder induced by cigarette smoke extract. Issue 1 (5th January 2016) - Liu, Yi; Wang, Bairu; Liu, Xinlu; Lu, Lu; Luo, Fei; Lu, Xiaolin; Shi, Le; Xu, Wenchao; Liu, Qizhan
Highlights: CSE enhances transfer of H3K27me3 to the p21 promoter via HOTAIR in HBE cells. CSE accelerates the G1/S transition by inhibiting p21 expression in HBE cells. Epigenetic silencing of p21 by HOTAIR is involved in CSE-induced cell cycle disorder. Abstract: Long noncoding RNAs (lncRNAs), which are epigenetic regulators, are involved in human malignancies. Little is known, however, about the molecular mechanisms for lncRNA regulation of genes induced by cigarette smoke. We recently found that, in human bronchial epithelial (HBE) cells, the lncRNA, Hox transcript antisense intergenic RNA (HOTAIR), is associated with changes in the cell cycle caused by cigarette smoke extract (CSE). In the present study, we report that increased expression of HOTAIR and enhancer of zeste homolog 2 (EZH2), and tri-methylation of Lys 27 of histone H3 (H3K27me3), affect cell cycle progression during CSE-induced transformation of HBE cells. Inhibition of HOTAIR and EZH2 by siRNAs attenuated CSE-induced decreases of p21 levels. Further, ChIP assays verified that HOTAIR and EZH2 were needed to maintain the interaction of H3K27me3 with the promoter regions of p21; combined use of a HOTAIR plasmid and EZH2 siRNA supported this observation. Thus, HOTAIR epigenetic silencing of p21 via EZH2-mediated H3K27 trimethylation contributes to changes in the cell cycle induced by CSE. These observations provide further understanding of the regulation of CSE-induced lung carcinogenesis and identify new therapeutic targets.